In vivo antidiabetic studies of wogonin isolated from the leaves of Tetracera indica Merr. - Afrin, Mehnaz (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2015)
The present thesis deals with the isolation, in vivo antidiabetic and toxicological evaluation of a flavonoid i.e. wogonin (5, 7-dihydroxy-8-methoxyflavone) isolated from the MeOH extract of Tetracera indica Merr. leaves (Dilleniaceae) (Mempelas paya in Malay) which is traditionally used in the management of diabetes in Malaysia. The thesis is therefore, presented in following three parts. Chemical investigation of the methanol extract (190 g) from the powdered leaves (1 kg) of T. indica resulted in the isolation of a desirable flavonoid i.e., wogonin (4.5 g). Isolation of the wogonin was carried out in three steps: multiple extractions with MeOH, fractionation using column chromatography and purification using recrystallization techniques with different polar solvents. Its structure was elucidated by spectroscopic analysis, mainly 1H-NMR, 13C-NMR, MASS, IR and UV techniques as well as comparison of the spectral data was made with those reported in the literatures for the same compound. In vivo antidiabetic study of wogonin was carried out using Sprague-Dawley rats (diabetic as well as normal) at three different concentrations (1, 5 and 25 mg/kg b.w.) At 5 and 25 mg/kg b.w., wogonin was found to exhibit significant anti-hyperglycaemic activity (p<0.05) in alloxan induced diabetic rats. In normal rats, no hypoglycaemic activity was observed at all the concentrations, when compared with +ve and –ve controlled groups. The antidiabetic activity was found to be comparable with glibenclamide (GLBC) (p<0.05), a known oral hypoglycemic agent (5 mg/kg b.w.). In vivo toxicological study was performed using the same strain of rats at two different concentrations (5 and 25 mg/kg b.w.) for continuous 15 days. During the study period no abnormal activity and mortality were observed. Histopathology of kidney, liver and pancreas of both normal and diabetic treated rats demonstrated normal and improved condition when compared to diabetic control group. The present study was also carried out to evaluate the effects of wogonin on biochemical parameters such as- kidney functional parameters (serum urea and creatinine) and serum lipid profile (TC, TG, LDL-C and HDL-C) parameters. There were no significant changes seen in the kidney and lipid functional parameters tested. This study has showed the significant efficacy of wogonin against diabetes without showing any toxicity. It is concluded that wogonin isolated from the leaves of T. indica is a safe and effective antidiabetic compound and may provide a chemical lead for the synthesis of new derivatives which might prove to be potential novel therapeutic agents in the treatment of diabetes.